The Perceived Corporate Social Responsibility of Major Sport Organizations by the German Public: An Empirical Analysis During the COVID-19 Pandemic - Tim F. Thormann; Pamela Wicker (Frontiers Media S.A., 2021)
Sport governing bodies have played a special role in society during the first wave of the COVID-19 pandemic. Following stakeholder theory and consumption capital theory, this study investigated the actions of the German Bundesliga (DFL), Union of European Football Associations (UEFA), and the International Olympic Committee (IOC) during this phase as perceived by the German population and through the lens of corporate social responsibility (CSR). Based on a representative sample of the German resident population (N = 1,000), the study examined the individual characteristics that influenced the perceived CSR of these organizations and what population clusters emerged from this perception. The survey applied a CSR scale that was previously validated in a professional team sports context. The results confirmed the equally strong applicability of the scale to the sport governing context. Cluster analysis yielded three distinctive clusters, namely, "supporters," "neutral observers," and "critics." Regression analyses and the cluster analysis identified those with frequent consumption and high involvement in sport as rating the actions of the three sport organizations more positively. They are also more strongly represented in the "supporters" cluster. In contrast, those threatened the most by the virus are overrepresented in the "critics" cluster.